'You're just one of the group when you're embedded': report from a mixed-method investigation of the research-embedded health librarian experience. - Greyson, Devon; Surette, Soleil; Dennett, Liz; Chatterley, Trish (Journal of the Medical Library Association, 2013)
Objective: Embedded librarianship has received much attention in recent years. A model of embeddedness rarely discussed to date is that of research-embedded health librarians (REHLs). This study explores the characteristics of Canadian REHLs and the situations in which they are employed. Methods: The authors employed a sequential, mixed- method design. An online survey provided descriptive statistics about REHLs' positions and work experiences. This informed a series of focus group interviews that expanded upon the survey. Through constant comparison, we conducted qualitative descriptive analysis of the interviews. Results: Based on twenty-nine survey responses and four group interviews, we created a portrait of a 'typical' REHL and discovered themes relevant to REHL work. REHLs may identify more strongly as researchers than as librarians, with corresponding professional needs and rewards. REHLs value 'belonging' to the research team, involvement in full project lifecycles, and in-depth relationships with nonlibrarian colleagues. Despite widely expressed job satisfaction, many REHLs struggle with isolation from library and information science peers and relative lack of job security. Conclusions: REHLs differ from non-embedded health librarians, as well as from other types of embedded librarians. REHLs' work also differs from just a decade or two ago, prior to widespread Internet access to digital resources. Implications: Given that research-embedded librarianship appears to be a distinct and growing subset of health librarianship, libraries, master's of library and information science programs, and professional associations will need to respond to the support and education needs of REHLs or risk losing them to the health research field.